Ocean acidification and warming modify stimulatory benthos effects on sediment functioning: An experimental study on two ecosystem engineers - Vlaminck, Ellen; Moens, Tom; Braeckman, Ulrike; Van Colen, Carl (Frontiers in Marine Science, 2023)
Many macrofauna have a stimulatory effect on sediment functioning through their burrowing, feeding and irrigation activities. Here, we investigated the single and combined effect of ocean acidification and warming on the stimulatory effect of two key-species inhabiting sandy seabeds in the Southern Bight of the North Sea; the bivalve Abra alba and the polychaete Lanice conchilega. The species were separately incubated in natural sediment in the laboratory under ambient, low pH (pH: -0.3), warm (T: + 3°C) and mimicked climate change (pH: -0.3, T: +3°C) conditions. After six weeks of incubation, nutrient and oxygen exchange were measured at the sediment-water interface to estimate aerobic sediment metabolism and nitrogen cycling. Both species facilitate sediment community oxygen consumption, nitrification and denitrification under ambient conditions. The stimulatory effect of A. alba disappeared in a low pH environment and decreased over time in the warmer treatments along with increased mortality. In contrast, L. conchilega stimulated sediment biogeochemical cycling more when seawater becomes acidified (+ 8 to 41%, depending on the function) but warming had no effect. We explain these species-specific climate change effects by different behavioral and physiological coping strategies that cascade on to sediment biogeochemical cycling, especially through altered oxygenation the sediment matrix.